Penerapan Digital Marketing Sebagai Strategi Pemasaran UMKM Studi Kasus Batik Tedjo - Riska Amalia; Siti Syaodah; Susilawati Susilawati; Riki Gana Suyatna (Jurnal Manuhara : Pusat Penelitian Ilmu Manajemen dan Bisnis, 2024)
Digital marketing has changed MSME players to continue to develop their business so that they are not left behind and are able to utilize this digital media, as an effort to market their products so that consumers are more familiar with the products produced by these MSMEs. Batik Tedjo is one of the MSMEs that plays a role in preserving written batik, which is one of the cultural heritages of the Indonesian nation. This study aims to determine how Batik Tedjo SMEs implement digital marketing and whether the implementation of digital marketing has obstacles. The problems faced by Batik Tedjo MSME players in implementing digital marketing show that there are problems in the form of a lack of understanding of social media operators at Batik Tedjo and the imbalance of consumer demand with human resources or a very minimal number of employees in managing Batik products which are quite a lot every month, reaching 200-300 pcs. The sample used in this study is the UMKM actor Father Tedi Sumantri Almargono, S.Pd. The results obtained from this study are digital-based marketing strategies carried out by Batik Tedjo to market its products using digital marketing. Its use is to post batik on social media such as Tiktok, Instagram, and Whatsapp. Making it easier for consumers to buy and get information about Batik Tedjo is through social media. Based on the analysis and results of the discussion, he